The macroeconomic fundamentals of the real exchange rate in Malaysia : some empirical evidence - J. M. Shukri; Muzafar Shah Habibullah; Roseziahazni Abdul Ghani; M. A. M. Suhaily (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this paper is to estimate the equilibrium of exchange rates and identify the roles of macroeconomics fundamentals affecting exchange rates using Malaysian data spanning 1970 to 2019. This study adopts the Autoregressive Distributed Lag model to examine the long-run relationships or cointegration among variables and the dynamic effect within variables in the short-run over the sample period. The results suggest that inflation rate and national income growth rate play important roles in influencing exchange rate movement. The results also reveal that the misalignment of exchange rates is quite small and stable during 1988 to 2019, except for 2015 which was attributed to the weaker growth in China. Consecutively, this study suggests that the parity condition is only important in the long-run in explaining exchange rates behaviour for the sample country.